2017
DOI: 10.1038/s41598-017-02030-6
|View full text |Cite
|
Sign up to set email alerts
|

Hyponatremia upon presentation to the emergency department – the need for urgent neuroimaging studies

Abstract: This study aims to evaluate the necessity of urgent neuroimaging for emergency admissions exhibiting symptomatology of profound hyponatremia. We retrospectively analyzed the medical records of all patients admitted to the emergency room of the University Hospital Münster from 2010 to 2014 with a serum sodium value < 125 mmol/L. From 52918 emergency admissions, 261 patients with profound hyponatremia were identified, of whom 140 (54%) had neurological symptoms. Unspecific weakness and confusion were the most pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…Our study showed that the use of ACEi/ARBs increases the risk of severe hyponatremia by 3.9 times compared to the risk of moderate hyponatremia (p � 0.027), which is in line with the fnding reported by Bhuvaneshwari et al, who concluded that hyponatremia was induced in nearly 50% of patients taking ACEi and ARBs, although the incidence of hyponatremia between patients receiving ACEi and those receiving ARBs were not statistically diferent [21]. In addition, they explained that the mechanism of ACEi-and ARB-induced hyponatremia has not been confrmed, but ACEi therapy increased the circulating angiotensin I that enters the brain and is converted into angiotensin II, which may stimulate thirst and release of antidiuretic hormone from the hypothalamus, eventually leading to hyponatremia [22,23].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study showed that the use of ACEi/ARBs increases the risk of severe hyponatremia by 3.9 times compared to the risk of moderate hyponatremia (p � 0.027), which is in line with the fnding reported by Bhuvaneshwari et al, who concluded that hyponatremia was induced in nearly 50% of patients taking ACEi and ARBs, although the incidence of hyponatremia between patients receiving ACEi and those receiving ARBs were not statistically diferent [21]. In addition, they explained that the mechanism of ACEi-and ARB-induced hyponatremia has not been confrmed, but ACEi therapy increased the circulating angiotensin I that enters the brain and is converted into angiotensin II, which may stimulate thirst and release of antidiuretic hormone from the hypothalamus, eventually leading to hyponatremia [22,23].…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, other reports showed that patients with profound hyponatremia usually show nonspecific neurological symptoms and may undergo neuroimaging examinations unnecessarily. Bokemeyer et al found that, among the 52,918 emergency admissions and 261 patients with profound hyponatremia, 140 (54%) had neurological symptoms [ 21 ]. Unspecific weakness and confusion were the most prevalent symptoms (59%).…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al found that the initial signs of patients who presented with hyponatremia were generalized weakness (33.3%), seizure (28.6%), altered mental status (21.6%), confusion (9.5%), dizziness (4.8%), and non-specific (2.4%) [ 10 ]. In Bokemeyer et al's study, of the 261 patients with hyponatremia, 140 exhibited neurological symptoms [ 11 ]. Most of these symptoms (59%) were general weakness and disorientation.…”
Section: Discussionmentioning
confidence: 99%
“…Hyponatraemia can present as a variety of FND including hemiparesis, monoparesis, rigidity, extrapyramidal type tremor, cerebellar ataxia, nystagmus and anisocoria [5] . It is also critical to remember that FND can be a sign of concurrent neurological disease including brain tumours, ischaemic stroke, intracranial haemorrhage and meningoencephalitis [6] . Therefore, a patient with FND in spite of hyponatraemia or other metabolic derangement should undergo neuroimaging to rule out other life-threatening conditions.…”
Section: Discussionmentioning
confidence: 99%